2011
DOI: 10.1177/1545109711399658
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Frail Patients in a Geriatric-HIV Program: The Experience of an Urban Academic Center at One Year Follow-Up

Abstract: We found that cognitive impairment, presence of comorbidities, high number of medications used, and past history of any opportunistic infection are factors prevalent in severely frail patients infected with HIV in our cohort. The significance of these factors in development and progression of frailty syndrome in HIV-positive patients needs to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
(16 reference statements)
1
10
0
1
Order By: Relevance
“…There is no reason why such a model would not work for ageing. This study has shown examples of geriatrician involvement as has other literature . There is also an increasing literature aimed at informing geriatricians of the issues pertinent to ageing in PLWH [).…”
Section: Discussionmentioning
confidence: 68%
“…There is no reason why such a model would not work for ageing. This study has shown examples of geriatrician involvement as has other literature . There is also an increasing literature aimed at informing geriatricians of the issues pertinent to ageing in PLWH [).…”
Section: Discussionmentioning
confidence: 68%
“…[25][26][27] Few shortterm outcomes are described, and we are unaware of data on concepts such as program acceptability, which is important for long-term programmatic success. [25][26][27] The field of implementation science can help address this knowledge gap, to allow for better understanding of how geriatric-HIV programs address age-related challenges in realworld clinical settings. Broadly, implementation science can be defined as the study of the strategies used to translate research knowledge into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“… 25 - 27 Few short-term outcomes are described, and we are unaware of data on concepts such as program acceptability, which is important for long-term programmatic success. 25 - 27 …”
Section: Introductionmentioning
confidence: 99%
“…Un total de 60 pacientes fueron evaluados para determinar la presencia de fragilidad-like (que consideró los dominios cognición, actividades básicas e instrumentadas de la vida diaria, estado nutricio, depresión, déficit auditivo, déficit visual y movilidad); de ellos, solo 20 ingresaron al programa (12 hombres y 8 mujeres con media de edad de 63.5 años) y fueron divididos en tres subgrupos según su grado de fragilidad: leve (20%) cuando había solo un dominio afectado, moderado (50%) con dos dominios afectados y grave (30%) con tres o más dominios afectados. En este estudio, al seguimiento de un año la mitad de los participantes desarrolló algún tipo de deterioro cognitivo, y los mayormente afectados fueron aquellos con un mayor grado de fragilidad, lo cual apoya la idea de la relación entre la intensidad de la fragilidad y el grado de deterioro cognitivo en los individuos con VIH 55 . En el mismo sentido, el estudio del Hospital HIV Clinic y del San Francisco Veterans Affairs Medical Center Infectious Diseases Clinic (155 participantes, 93.6% hombres y con media de edad de 57 años) mostró la presencia de fragilidad en un 9% y de deterioro cognitivo en un 46.7%, lo cual es un reflejo de la alta prevalencia de estas dos afecciones vistas común-mente en el adulto mayor, pero también entre una población relativamente joven con VIH+ 56 .…”
Section: Deterioro Cognitivo En Personas Con Vih Y Fragilidadunclassified